Reuse of port industrial heritage in tourist cities: Shipyards as case studies. - Andrade-Marqués, María José; Jiménez-Morales, Eduardo; Rodríguez-Ramos, Rachel; Martínez-Ramírez, Pablo (Elsevier, 2024)
The progressive deindustrialisation of many western cities since the 1980s has led to many industrial zones linked to port activities being abandoned or falling into disuse. Cities such as Barcelona, Naples, Lisbon, Amsterdam, and Hamburg have port industrial complexes of high tangible and intangible heritage value that could totally or partially disappear, resulting in an irreparable loss of their scientific, architectural, social, technological, and historical values. With that in mind, Adaptive Reuse (AR) of the built heritage allows the industrial memory of the ports to be preserved by turning them into new functional centres within the existing urban structure. That occurs in the context of the contemporary challenges of those cities, such as touristification, the circular economy and climate change, while guaranteeing the life cycle of those buildings. This article analyses two case studies—the Nederlandsche Scheepsbouw Maatschappij (NDSM) and the Rotterdamsche Droogdok Maatschappij (RDM) shipyards, both in the Netherlands—in order to contribute to the knowledge of AR of Port Industrial Heritage. They are two examples of good practices in port industrial heritage interventions, where the factors behind their acclaim can be easily highlighted. A multi-scale methodology is therefore used and tailored to the case of port industrial heritage, based on analysing previous studies of the heritage in different spheres and on different scales. A relationship matrix tool is thus defined. It enables a comparative study to be conducted, using key variables and indicators, and considering qualitative and quantitative data. That provides extensive output information for each case study, which is summarised in the most favourable factors for the success of the AR of this port industrial heritage.
Keywords: Patrimonio industrial; Astilleros - Estudio de casos; Gentrificación; Industrial heritage; Port-city; Adaptive reuse; Best practices; Circular economy; HUL; Touristification